2008
DOI: 10.1016/j.biomaterials.2007.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Osteotropic β-cyclodextrin for local bone regeneration

Abstract: An osteotropic alendronate-β-cyclodextrin conjugate (ALN-β-CD) was developed as a bonetargeting delivery system for improved treatment of skeletal diseases. The conjugate shows very strong binding to hydroxyapatite (HA, main component of the skeleton). Its ability in forming molecular inclusion complex with prostaglandins E 1 (PGE 1 , a potent bone anabolic agent) was confirmed by phase-solubility experiments and differential scanning calorimetry (DSC). In a bilateral rat mandible model, ALN-β-CD/PGE 1 molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
(27 reference statements)
0
33
1
Order By: Relevance
“…Being considered biologically inert, CDs have been approved by US FDA as pharmaceutical excipients for numerous drug formulations [12]. Recently, the study of Liu et al [13] even surprisingly reported that in vivo some b-CD derivative showed a robust bone anabolic effect. Therefore, CDs could be applied as drug carrier on bone substitute material for conferring antibacterial properties to them, and also probably further favor the bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Being considered biologically inert, CDs have been approved by US FDA as pharmaceutical excipients for numerous drug formulations [12]. Recently, the study of Liu et al [13] even surprisingly reported that in vivo some b-CD derivative showed a robust bone anabolic effect. Therefore, CDs could be applied as drug carrier on bone substitute material for conferring antibacterial properties to them, and also probably further favor the bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…For Van-loaded mPEG-PLGA micelle, the relative absorbance of the solutions treated and not treated with HA were 83% and 90%, which did not show statistical difference, implying no specific adhesion of mPEG-PLGA micelles to HA surface took place. Since the P-C-P bond and the hydroxyl group of the ALN play major roles in the affinity of ALN to HA, [29,30] no much difference was observed for the affinity test performed at pH 5.0 ( Figure 6B) from that at pH 7.4. Therefore, the binding affinity was not influenced by the external pH.…”
Section: Ha Affinity Testmentioning
confidence: 92%
“…The interactions with other molecules may also be utilized to provide the surface with a drug release capability [13,14]. Another beneficial effect of cyclodextrins was discovered by Liu et al [15] who for some b-cyclodextrin derivatives could document an anabolic effect on bone.…”
Section: Introductionmentioning
confidence: 99%